Crowd on the National Mall - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows crowd on the National Mall at the National March on Washington for Lesbian and Gay Rights. Members of the crowd hold up banners that read, "Ann Arbor says closets are [for clothes?]", "Dykes opposed to nuclear technology" and "Gay rights". The base of the Washington Monument appears in the background.